A group dance that never ends a pluriversal approach to "Continuum - Generation by Generation" (2017) - Hopfener, Birgit (2024)
How did the exhibition in the Chinese pavilion at the 57th Venice Biennale entitled Continuum – Generation by Generation (buxi 不息) mobilize the concept of buxi, which translates literally as "endlessness" or "never ceasing"? What does it mean to conceive of art, the world, and oneself through the lens of buxi, as endlessly intrarelated? This paper delves into this question from a multi-pronged perspective. First, it explains the meaning of buxi and analyzes how the show engages with aesthetic, epistemological, social and political implications of art and the world conceived through a contemporary perspective on the concept of "endlessness". Second, the paper explores how a reading of the show and the artworks – their adopted aesthetic strategies, media, techniques, and materialities – through the lens of buxi complicates the critical and aesthetic framework for contemporary art in the global context. Finally, the paper evaluates the engagement with buxi – and the respective alternative processual ontology and temporality of art and world – as a useful mode of decolonizing the discipline of art history, even as it emphasizes the importance of adopting a dynamic pluriversal approach that attends to the transcultural relations that shape and reshape the multiplicity of meanings of art in a global framework, its multiple and entangled critical and aesthetic discourses, and the complexity of power structures, and avoids obscuring significant contexts and experiences
Keywords: Biennale di Venezia -- 57. -- 2017 -- Venedig; Thema; Kunst; Unendlichkeit; China; Buxi; Dekolonial; Verwoben; Unbeständigkeit; Ineinandergreifend; Pluriversal; Zeitliche Struktur der Unendlichkeit (Buxi); Transkulturell